Dari Iqra’ sampai Quantum: Upaya Kreatif Pengembangan Strategi Pembelajaran - Moh. Roqib (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
There are many efforts from Islamic education expert and practitioner to make student happy and easy to learn. From several strategy, Iqra’ model and quantum get much attention in Indonesia. Electivity and efficiency of this strategy have been acknowledged. Therefore, innovation has always been supported without abandon past learning strategy or classical strategy that has been practiced by pesantren and school. From Islamic education perspective, this article supposed to thrust enthusiasm to all to create and apply other creative innovation. .